The Effect of Breeding Flock Age on Fattening Performance and Carcass Characteristics in Broiler - Kurşun, Kadriye; Durmuş, Murat; Baylan, Mikail (Turkish Journal of Agriculture - Food Science and Technology, 2022)
In this study conducted to investigate the effect of breeding flock age on the fattening performance and carcass characteristics of broilers, Ross-308 chicks obtained from the eggs of breeding in three different age groups; young (30 weeks old), middle (47 weeks old), and old (59 weeks old) were used. For this purpose, three different treatment groups and three replications in each treatment group were formed depending on the breeder age in the experiment. In the study, 30 chicks in each replication, 90 chicks in each treatment group and 270 chicks in total were used. At the initial and the end of the experiment, the differences observed between the treatment groups in terms of live weight were found to be significant. It was determined that chick live weights per trial increased with increasing flock age (P<0.05). However, it was determined that the highest feed consumption and live weight gain was in the chickens obtained from old flocks and the feed conversion ratio of this group was higher than the other groups (P>0.05). As a result, although chicks obtained from old flocks had higher live weight at the beginning of the experiment, the effect of flock age on fattening performance and carcass parameters was eliminated at the end of the experiment and showed similar values with the chicks obtained from medium and young flocks.